(untitled) (Research, Society and Development, 2026)
The objective of this study was to evaluate the stability, antioxidant, colorimetry and infrared activity of the phenolic compounds of Spirulina-18. The phenolic extract was obtained from the extraction with the solvent methanol, and two samples were used, one stored under refrigeration at 4ºC and the other subjected to high temperatures during the period of six months (180 days) were evaluated by quantifying the content of total phenols in the extract, subsequently, it was performed by spectrophotometry, using the Folin-Ciocalteau reagent, which was determined by interpolation of the absorbances of the samples, in relation to an analytical curve constructed with a standard solution of gallic acid, at a concentration of 10 to 100μg/ml. The absorbances of the solutions were measured at 750 nm. An increase in the content of phenolic compounds was observed during the three months of storage under refrigeration of 4ºC. Therefore, refrigeration did not affect the amount of total phenols during the storage period. In the calorimetry, the influence of pH on the extract was verified. The FTIR analysis of the extract identified the functional groups existing in the structure of the phenolic compounds.